Pengaruh Word of Mouth, Kualitas Produk dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada E-Commerce TikTok Shop di Kota Batam - Siallagan, Dwi Natalia Angela; Wasiman, Wasiman (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The rapid development of digital platforms has significantly influenced consumer behavior, particularly in the beauty industry. However, inconsistencies in product quality and customer trust have raised concerns regarding online purchasing decisions. This study aims to examine the influence of word of mouth, product quality, and consumer trust on purchasing decisions for Pixy cushion products via the TikTok Shop in Batam City. A quantitative method with a descriptive approach was applied. Data were collected from 100 respondents selected using purposive sampling criteria and analyzed using SPSS version 26. The research instruments passed both validity and reliability tests. The analysis included classical assumption testing, multiple linear regression, and hypothesis testing through t-tests and F-tests. The results indicate that all three independent variables word of mouth, product quality, and consumer trust have a positive and statistically significant effect on consumer purchasing decisions, both individually and collectively. The adjusted R² value of 0.805 suggests that 80.5% of the variation in purchasing decisions is explained by the three predictors. Among them, consumer trust had the highest standardized coefficient (β = 0.433), followed by product quality (β = 0.353) and word of mouth (β = 0.225). These findings highlight the strategic importance of maintaining product credibility and fostering consumer trust in the social commerce ecosystem.